Saline water concentration determines the reduction pathway for oat phosphorus absorption - Tong Liu; Lihua Xia; Xinliang Dong; Jintao Wang; Xiaojing Liu; Hongyong Sun; Yunying Fang (Agricultural Water Management)
Saline water irrigation offers a potential solution for sustaining crop yields under freshwater scarcity. However, it carries risks such as soil structure deterioration and soil organic matter decomposition, which could accelerate nutrient release. Elevated soil salinity further hampers crop growth and reduces nutrient uptake, particularly affecting phosphorus absorption. This study investigated the dynamics of soil pH, electrical conductivity, water content and available phosphorus throughout the entire growth period of oat treated with 1, 3, and 5 g L−1 saline water. It also examined the post-harvest responses of soil aggregates and their associated phosphorus, as well as the above-ground biomass and phosphorus content in various oat organs. The results showed that 1) Compared to the 1 g L−1, 3 and 5 g L−1 treatments significantly increased soil electrical conductivity and water content throughout most of the growth period, with the 5 g L−1 treatment also significantly increasing soil available phosphorus content; 2) The 3 and 5 g L−1 treatments significantly reduced the soil macro-aggregate (>1 mm) proportion by 24.76 % and 36.36 % (p < 0.05), while increasing soil micro-aggregate (<0.053 mm) by 39.41 % and 71.59 % (p < 0.05), along with higher available phosphorus content in the < 0.053 mm fraction; 3) The above-ground phosphorus content in oats decreased by 30.27 % and 35.39 % under the 3 and 5 g L−1 treatments, respectively, compared to the 1 g L−1 treatment. Partial least squares structural equation modeling revealed the different reduction pathways: 3 g L−1 saline water inhibited crop phosphorus absorption by reducing phosphorus concentrations in stem and shell (Path coefficient [PC] = 0.796, p < 0.001), whereas 5 g L−1 reduced it by decreasing the stem and seed biomass (Path coefficient [PC] = 0.816, p < 0.001). This study reveals the effects of saline water irrigation on soil and crop phosphorus availability, providing valuable insights for optimizing saline water use and enhancing phosphorus availability in agricultural systems.